The Effects of Two Different Cleaning and Disinfection Programs on Broiler Performance and Microbiological Status of Broiler Houses - Burbarelli,MFC (2015)
ABSTRACT The objective of this study was to investigate the influence of two cleaning and disinfection programs on broiler performance and on the microbiological status of the facilities. This trial was an observational study of comparative character. Two experiments were conducted, with 960 birds each. Both experiments were carried out in a positive-pressure broiler house. Broilers were distributed in pens equipped with a bell drinker and a tube feeder each. In the first experiment, new wood shavings were used as litter material, and in the second, reused wood shavings were used. Two treatments with16 replicates of 30 birds each were evaluated. The regular treatment consisted of dry and wet organic matter removal, followed by washing. The European treatment consisted of dry organic matter removal, humidification, washing with water under high pressure, detergent application, rinsing, and application of two combined disinfectants: glutaraldehyde 250g/L + formaldehyde 185g/L; p-chlor-m-cresol 210 g/L. Biosecurity measures were adopted during daily management tasks to prevent cross contamination between treatments. The effectiveness of the treatments was evaluated by microbiological analysis performed before and after treatment applications, as well as by broiler performance results. Live performance results were similar between both treatments when broilers were reared on new litter. When reused word-shavings were used as litter material, the European treatment promoted better broiler performance. The European treatment was more effective than the regular treatment in reducing total microbial counts in the facilities when reused wood shavings were used as litter material, and positively influenced broiler performance.